VALIDITAS PERJANJIAN ELEKTRONIK DALAM SISTEM HUKUM INDONESIA: ANALISIS NORMATIF TERHADAP KERANGKA HUKUM, YURISPRUDENSI, DAN TANTANGAN IMPLEMENTASI - Poetri Enindah Suradinata; Charles Rory; Muhammad Ihsan (Astha Grafika, 2026)
The development of digital technology has transformed the paradigm of legal transactions, notably through the emergence of electronic contracts. Utilizing a normative-empirical legal research method with statutory, conceptual, and case approaches, this study aims to analyze the validity of electronic contracts within the Indonesian positive legal system, jurisprudential trends, and implementation challenges. The results indicate that although the Law on Electronic Information and Transactions (UU ITE) provides a legal basis recognizing electronic contracts as valid evidence, practical implementation still faces various technical, legal, and social hurdles. Jurisprudence shows a growing acceptance of digital contracts, yet inconsistencies in court applications persist. The primary challenges include data security, digital literacy, and regulatory ambiguity surrounding smart contracts and cryptocurrency. This study recommends a comprehensive revision of the UU ITE, optimization of Personal Data Protection Law implementation, and the development of alternative online dispute resolution (ODR) systems to support an inclusive and equitable digital legal ecosystem.